The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jscm.12247
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing Social Sustainability: Signaling Theory Insights into Supplier Selection Decisions

Abstract: Social sustainability has emerged as a key determinant in supplier selection. However, firms may approach social sustainability in varying ways such as investments in employee welfare or philanthropy. Little is known about how supply chain managers consider these individual dimensions when making sourcing decisions. Therefore, this research decomposes social sustainability into dimensions of employee welfare and philanthropy to determine their effects on supplier selection. Vignette-based experiments in a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…Barker and Brau, 2020; Fugate et al. , 2012; Thomas et al , 2021) and allow for control over differences in organizations and supply chains that naturally occur in survey and case-based research. In experiments, vignettes contain common elements but have scenarios in which the variables of interest have different levels (Rungtusanatham et al.…”
Section: Methodology and Findings: Testing Initial Propositions Using...mentioning
confidence: 99%
“…Barker and Brau, 2020; Fugate et al. , 2012; Thomas et al , 2021) and allow for control over differences in organizations and supply chains that naturally occur in survey and case-based research. In experiments, vignettes contain common elements but have scenarios in which the variables of interest have different levels (Rungtusanatham et al.…”
Section: Methodology and Findings: Testing Initial Propositions Using...mentioning
confidence: 99%
“…Therefore, signaling theory underpins the idea that the buyer's trust toward the supplier is associated with various trustworthiness signals in the buyer-supplier relationship. Previous supply chain studies have identified reputation (Wagner et al, 2011) and social sustainability initiatives (Thomas et al, 2021) as signals leading to supplier trust. In our context, following recent literature proposing blockchain implementation as a creditworthiness signal in supply chain finance (Chod et al, 2020), we further extend this signaling effect to the context of buyer-supplier relationship governance and argue that the implementation of blockchain can also signal the trustworthiness of the supplier.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…By exploring blockchain's role as a trustworthiness signal, we extend the emerging research stream on the signaling effects of blockchain to the relational dimension of supply chain management (Chod et al, 2020). Moreover, previous supply chain research has explored some signaling antecedents of trust in a buyer-supplier relationship like supplier reputation (Wagner et al, 2011) and social sustainability (Thomas et al, 2021), yet our understanding of the interaction between trustworthiness signals and other antecedents of trust like norms are limited. This knowledge gap also echoes the emerging debate around (in)congruence across multidimensional signals describing similar characteristics (Paruchuri et al, 2021).…”
Section: Theoretical Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…We employ middle‐range theorization, using top–down theoretical contextualization (Craighead et al, 2016; Stank et al, 2017) to explain how the positive signal of SCT and the negative signal of a product recall constitute an interdimensional set of incongruent signals that impacts consumers' product quality perceptions and repurchase intentions. Signaling theory is well established in management research, and increasingly being employed in supply chain management research to explore sustainability issues (e.g., Duan, Aloysius, & Mollenkopf, 2022; Duan, Hofer, & Aloysius, 2021; Hofer et al, 2012; Jacobs, 2014; Ketchen et al, 2014; Thomas et al, 2021). Therefore, the sustainable supply chain context provides fertile ground for examining SCT as a mechanism for constructive engagement between firms and consumers.…”
Section: Introductionmentioning
confidence: 99%